Induction of reproduction of fish Anasa Nomorhampus sp. endemic Palu, Central Sulawesi orally through hormon bioencapsulation use Chironomus sp. - Rezki, Dinda Wahyu; Sudrajat, Agus Oman; Soelistyowati, Dinar Tri; Carman, Odang (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
Species Nomorhampus sp. with the local name Anasa fish, endemic to Palu, Central Sulawesi, has a unique superior mouth shape, beak-shaped jaws, attractive colors and patterns, becoming an export commodity with high economic value, but currently it cannot be cultivated, domestication efforts are needed to avoid extinction, by carrying out hormonal manipulation that accelerates the domestication process. This study aims to evaluate the effectiveness of Oodev® on the induction of reproduction in the fish Nomorhampus sp. through bioencapsulation using Chironomus sp. which resulted in births, five groups of fish were fed using Oodev® at a dose of 1 mL/kg parent weight and NaCl 1 mL/kg parent weight as a control group, the fish were kept for 60 days. This research focuses on assessing specific weight growth rate (LPBS), specific length growth rate (LPPS), survival rate (TKH), gonadosomatic index (IGS), gonadal histology, birth frequency, number of births, and growth performance. Fish fed Oodev® feed showed higher SGR and IGS (p<0.05), 40% of fish fed Oodev® supplementary feed successfully gave birth with a total of 9 fry, while no birth occurred in control fish. Histological analysis showed faster gonad development in fish fed Oodev®. Hormonal induction with Oodev® can accelerate reproduction in anasa fish in cultivation containers. These findings provide valuable insight for fish farmers regarding the effect of Oodev® on gonad development in anasa fish in both male and female parents. It is hoped that this discovery will speed up the process of domestication of Anasa fish. Keywords: domestication, endemic, Nomorhampus sp., Oodev®, reproduction ABSTRAK Spesies Nomorhampus sp. dengan nama lokal ikan Anasa endemik Palu, Sulawesi Tengah, memiliki keunikan bentuk mulut superior rahang berbentuk paruh, warna dan corak menarik menjadi komoditas ekspor dengan nilai ekonomis yang tinggi, namun saat ini belum dapat dibudidayakan, perlu upaya domestikasi agar tidak terjadi kepunahan, dengan melakukan manipulasi hormormonal yang mempercepat proses domestikasi. Penelitian ini bertujuan untuk mengevaluasi efektivitas Oodev® terhadap induksi reproduksi ikan Nomorhampus sp. melalui bioenkapsulasi menggunakan Chironomus sp. yang menghasilkan kelahiran, lima kelompok ikan yang diberi pakan menggunakan Oodev® dosis 1 mL/kg bobot induk dan NaCl 1 mL/kg bobot induk sebagai kelompok kontrol, ikan dipelihara selama 60 hari. Penelitian ini fokus pada penilaian laju pertumbuhan bobot spesifik (LPBS), laju pertumbuhan panjang spesifik (LPPS), tingkat kelangsungan hidup (TKH), indeks gonadosomatik (IGS), histologi gonad, frekuensi kelahiran, jumlah kelahiran, dan kinerja pertumbuhan. Ikan yang diberi pakan Oodev® menunjukkan SGR dan IGS yang lebih tinggi (p<0,05), 40% ikan yang diberi pakan tambahan Oodev® berhasil melahirkan dengan jumlah total 9 ekor benih, sementara pada ikan kontrol tidak terjadi kelahiran. Analisa histologi menunjukkan perkembangan gonad yang berkembang lebih cepat pada ikan yang diberi pakan Oodev®. Induksi hormonal dengan Oodev® mampu mempercepat reproduksi pada ikan anasa di wadah budidaya. Temuan ini memberikan wawasan berharga bagi pembudidaya ikan mengenai pengaruh Oodev® terhadap perkembangan gonad pada ikan anasa baik pada induk jantan maupun betina. Penemuan ini diharapkan dapat mempercepat proses domestikasi ikan Anasa. Kata kunci: domestikasi, endemik, Nomorhampus sp., Oodev®, reproduksi